2015
DOI: 10.5045/br.2015.50.1.51
|View full text |Cite
|
Sign up to set email alerts
|

HBV reactivation in a HBsAg-negative patient with multiple myeloma treated with prednisolone maintenance therapy after autologous HSCT

Abstract: Hepatitis B virus (HBV) reactivation has previously occurred in hepatitis B surface antigen-negative patients with malignant lymphoma who received rituximab-based combination chemotherapy. However, few reports have described cases of HBV reactivation in patients with multiple myeloma thus far. We report a case of HBV reactivation in a patient with multiple myeloma treated with chemotherapy, autologous hematopoietic stem cell transplantation, and maintenance steroid therapy. For the HBV reactivation, the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The risk of HBV reactivation is well described in patients with lymphoma, especially after the use of rituximab (reference). However, for MM there are just a few case reports that described the risk of HBV reactivation after cytotoxic chemotherapy 38,39 , 19,40 . In these case reports most patients were receiving steroids, proteasome inhibitors or immunomodulatory agents, and very few had undergone an auto-HCT 38,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HBV reactivation is well described in patients with lymphoma, especially after the use of rituximab (reference). However, for MM there are just a few case reports that described the risk of HBV reactivation after cytotoxic chemotherapy 38,39 , 19,40 . In these case reports most patients were receiving steroids, proteasome inhibitors or immunomodulatory agents, and very few had undergone an auto-HCT 38,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 9 10 ] However, bortezomib-based regimens usually contain glucocorticoid, which has a negative effect on HBV infection, [14] and maintenance therapy with prednisolone can also result in HBV reactivation in patients of multiple myeloma. [15] Moreover, studies have shown that autologous HSc transplantation is one of the important risk factors for HBV reactivation. [ 16 17 ] These factors also influence the assessment of the role of bortezomib in HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective reports summarizing HBV reactivation in MM patients, including case reports, included a total of 125 cases [8,22,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68] (Table 4 and Table 5). All 16 cases with HBV reactivation through 2010 underwent HSCT [56,57,58,59,60,61].…”
Section: Hbv Reactivation In MM Patientsmentioning
confidence: 99%